Linear Phase Velocity Effect on Accumulation of Zinc in Homogeneous Fine Sand Applying Predictive Model - F. E., Ezeilo; S. N., Eluozo (International Journal For Research In Mechanical & Civil Engineering, 2018)
The behaviour of velocity in predominant sand gravel was observed to affect the accumulation of zinc in sand gravel deposition; the concept of this study was to monitor the rate of zinc deposition pressured by linear fluids velocity deposition in sand gravel formation. Base on these factors, zinc deposition in sand gravel through velocity of flow pressure experiences slight fluctuations in some deposited depths of the formations; these are observed where linear velocity of flow was found predominant. The effect on zinc deposition also observed variations of velocities base on the stratification as it is expressed on the lithology. The formations in some locations experiences low velocities thus zinc concentration where very high in these few simulated results. The developed model generated theoretical values. Simulation results show that zinc concentration varies from 1.12 to 10.4 mg/l , 8.49E-05 mg/l to1.19E-03mg/l and 4.77E-03mg/l to 6.32 E-03mg/s at depths of 3-30metres and 3-36metres respectively. These data were compared with experimental values and both parameters compared favourably well. Experts in soil and water engineering will definitely use this concept as a tool in design of environmental systems.